Answer
Verified
483.9k+ views
Hint: Prove the R.H.S. of each statement is equal to the L.H.S. of the statement. Use the fact that $A-B=A\bigcap {{B}^{c}}$. Use distributive laws and associative laws of union and intersection to simplify R.H.S. and hence prove L.H.S. is equal to R.H.S.
Complete step-by-step answer:
[i] We have R.H.S. $=\left( A-C \right)\bigcup \left( B-C \right)$
We know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have R.H.S. $=\left( A\bigcap {{C}^{c}} \right)\bigcup \left( B\bigcap {{C}^{c}} \right)$
We know that the intersection of two sets distributes over the union, i.e. $A\bigcap \left( B\bigcup C \right)=\left( A\bigcap B \right)\bigcup \left( A\bigcap C \right)$
Hence, we have
R.H.S. $={{C}^{c}}\bigcap \left( A\bigcup B \right)$
Now, we know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have R.H.S. $=A\bigcup B-C$
Hence, RHS = LHS.
[ii] RHS $=\left( A-C \right)\bigcap \left( B-C \right)$
We know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have R.H.S. $=\left( A\bigcap {{C}^{c}} \right)\bigcap \left( B\bigcap {{C}^{c}} \right)$
We know that the intersection of two sets is associative, i.e. $A\bigcap \left( B\bigcap C \right)=\left( A\bigcap B \right)\bigcap C$
Hence, we have R.H.S. $=A\bigcap \left( {{C}^{C}}\bigcap \left( B\bigcap {{C}^{c}} \right) \right)$
We know that the intersection of two sets is associative, i.e. $A\bigcap \left( B\bigcap C \right)=\left( A\bigcap B \right)\bigcap C$
Hence, we have R.H.S. $=A\bigcap \left( \left( {{C}^{c}}\bigcap {{C}^{c}} \right)\bigcap B \right)$
We know that $A\bigcap A=A$
Hence, we have
R.H.S. $=A\bigcap \left( {{C}^{c}}\bigcap B \right)=A\bigcap \left( B\bigcap {{C}^{c}} \right)$
We know that the intersection of two sets is associative, i.e. $A\bigcap \left( B\bigcap C \right)=\left( A\bigcap B \right)\bigcap C$
Hence, we have
R.H.S. $=\left( A\bigcap B \right)\bigcap {{C}^{c}}$
Now, we know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have
R.H.S. $=A\bigcap B-C$
Hence, LHS = RHS
Note: Verification using Venn diagrams:
[i] Diagram of $A\bigcup B$
Complete step-by-step answer:
[i] We have R.H.S. $=\left( A-C \right)\bigcup \left( B-C \right)$
We know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have R.H.S. $=\left( A\bigcap {{C}^{c}} \right)\bigcup \left( B\bigcap {{C}^{c}} \right)$
We know that the intersection of two sets distributes over the union, i.e. $A\bigcap \left( B\bigcup C \right)=\left( A\bigcap B \right)\bigcup \left( A\bigcap C \right)$
Hence, we have
R.H.S. $={{C}^{c}}\bigcap \left( A\bigcup B \right)$
Now, we know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have R.H.S. $=A\bigcup B-C$
Hence, RHS = LHS.
[ii] RHS $=\left( A-C \right)\bigcap \left( B-C \right)$
We know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have R.H.S. $=\left( A\bigcap {{C}^{c}} \right)\bigcap \left( B\bigcap {{C}^{c}} \right)$
We know that the intersection of two sets is associative, i.e. $A\bigcap \left( B\bigcap C \right)=\left( A\bigcap B \right)\bigcap C$
Hence, we have R.H.S. $=A\bigcap \left( {{C}^{C}}\bigcap \left( B\bigcap {{C}^{c}} \right) \right)$
We know that the intersection of two sets is associative, i.e. $A\bigcap \left( B\bigcap C \right)=\left( A\bigcap B \right)\bigcap C$
Hence, we have R.H.S. $=A\bigcap \left( \left( {{C}^{c}}\bigcap {{C}^{c}} \right)\bigcap B \right)$
We know that $A\bigcap A=A$
Hence, we have
R.H.S. $=A\bigcap \left( {{C}^{c}}\bigcap B \right)=A\bigcap \left( B\bigcap {{C}^{c}} \right)$
We know that the intersection of two sets is associative, i.e. $A\bigcap \left( B\bigcap C \right)=\left( A\bigcap B \right)\bigcap C$
Hence, we have
R.H.S. $=\left( A\bigcap B \right)\bigcap {{C}^{c}}$
Now, we know that $A-B=A\bigcap {{B}^{c}}$
Hence, we have
R.H.S. $=A\bigcap B-C$
Hence, LHS = RHS
Note: Verification using Venn diagrams:
[i] Diagram of $A\bigcup B$
Diagram of $A\bigcup B-C$
Diagram of $A-C$
Diagram of $B-C$
Diagram of $\left( A-C \right)\bigcup \left( B-C \right)$
Hence from Venn diagrams, it is verified that $\left( A\bigcup B \right)-C=\left( A-C \right)\bigcup \left( B-C \right)$
Similarly, it can be verified from Venn diagrams that $\left( A\bigcap B \right)-C=\left( A-C \right)\bigcap \left( B-C \right)$
Similarly, it can be verified from Venn diagrams that $\left( A\bigcap B \right)-C=\left( A-C \right)\bigcap \left( B-C \right)$
Recently Updated Pages
Identify the feminine gender noun from the given sentence class 10 english CBSE
Your club organized a blood donation camp in your city class 10 english CBSE
Choose the correct meaning of the idiomphrase from class 10 english CBSE
Identify the neuter gender noun from the given sentence class 10 english CBSE
Choose the word which best expresses the meaning of class 10 english CBSE
Choose the word which is closest to the opposite in class 10 english CBSE
Trending doubts
Fill the blanks with the suitable prepositions 1 The class 9 english CBSE
Which are the Top 10 Largest Countries of the World?
Change the following sentences into negative and interrogative class 10 english CBSE
Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE
10 examples of friction in our daily life
How do you graph the function fx 4x class 9 maths CBSE
Give 10 examples for herbs , shrubs , climbers , creepers
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
What is pollution? How many types of pollution? Define it